Altered ground reaction forces in individuals with chronic ankle instability compared to lateral ankle sprain copers and healthy controls during walking - Lee, I.; Ha, S.; Lee, S. Y. (Korean Journal of Sport Biomechanics, 2023)
Objective: Few studies have investigated alterations of ground reaction force (GRF) in individuals with chronic ankle instability (CAI) compared with lateral ankle sprain (LAS) copers and healthy controls during walking. This study aimed to investigate differences in GRF variables among the CAI, LAS coper, and control groups. Method: Eighteen individuals with CAI, 18 LAS copers, and 18 healthy controls were recruited for this study. All participants walked on 8-m walkway with a force plate three times. GRF data during stance phase were extracted and analyzed. The analysis of variance and ensemble curve analysis were used for statistical analyses of discrete points and time-series data respectively. Results: The CAI group showed a greater loading rate (LR) and a shorter time to impact peak force than the other groups, as well as decreased vGRF from 56% to 65% in the stance phase than the control group. No significant differences were noted in the other variables. Conclusion: Based on these findings, individuals with CAI should enhance their ability to create propulsion during the push-off phase and spend more time absorbing GRF to decrease the LR, which is considered one of risk factors for overuse injury and ankle osteoarthritis.